THE MEANING OF á¹¢ALÄ€T IN AL-QUR'AN: Semantic Analysis of Toshihiko Izutsu - Syafirin, Muhammad (Jurnal AlifLam Journal of Islamic Studies and Humanities, 2020)
This article discusses the meaning of á¹£alÄt in the Qur'an. So far, the word of á¹£alÄt has only been interpreted in terms of ritual worship alone. In reality, the meaning of á¹£alÄt in the Al-Qur'an has many meanings. To reveal this variant of meaning, the semantic theory of Toshihiko Izutsu was used in the concept of weltanschauunglehrer and elaborated with literature study-based research which made the Al-Qur'an as the primary material and the commentaries as secondary material. After going through several stages of research, the word á¹£alÄt in the Al-Quran has several equivalent meanings, such as the words al-dzikr, al-istighfar, al-sujud, and al-Qur'Än. Meanwhile, the antonym of the á¹£alÄt is sÄhÃ»n and mujrimÃ»n.